Poverty reduction programs in rural Sarawak: case study Asajaya Samarahan / Abdul Kamis Tawa & Rellyn Neena Allen James - Tawa, Abdul Kamis; Allen James, Rellyn Neena (2014)
Ever since independence in 1957, Malaysia has successfully transformed itself from a poor country into a middle-income nation. The Malaysian economy has seen a periodic growth despite challenging external factors. It can also definitely claim its success of combat against poverty. Despite its poverty reduction success, there still remains a vulnerable group of people in the country experiencing poverty for some geographical and societal reasons such as in Sarawak. The concept of this study is about the poverty reduction programs in rural Sarawak: Case study Asajaya, Samarahan. Sarawak state has one of the highest poverty rates in Malaysia, 2010 since independence especially in the rural area. According to Kalantari et.al. 2008, rural area and poor communities almost a synonym for the agricultural sector (Nor Diana M.l, Chamhuri S, Bash A.B, Madeline B, 2012). It is clearly specify in order to achieve sustainable livelihood in rural communities, poverty reduction through sustain the economic viability of farm operation, satisfy human food and fibre needs and enhance the quality of life for farmers and society as a whole ( Murad et al., 2008). Therefore, sustainable rural development in the agricultural sector often receives attention in the planning agenda of poverty eradication program in Malaysia through various government programs. (Hashim, 1996).